1993
DOI: 10.1038/ng0993-74
|View full text |Cite
|
Sign up to set email alerts
|

The insulin–like growth factor type–2 receptor gene is imprinted in the mouse but not in humans

Abstract: In mouse, four genes have been found to undergo genomic imprinting resulting in differential expression of maternally and paternally inherited alleles. To determine whether the cognate genes are also subject to imprinting in humans, we have studied allele-specific expression patterns of insulin-like growth factor 2, IGF2-receptor and H19 in human fetal and adult tissues. In keeping with previous findings in mice, our results indicate that in human fetal tissues the paternal H19 alleles is inactive. IGF2 is mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
0
2

Year Published

1996
1996
1998
1998

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 234 publications
(127 citation statements)
references
References 33 publications
8
117
0
2
Order By: Relevance
“…Differences in chromatin structure as well (Rabin et aL, 1987). The observation that paternal (Welch et aL, 1990) and maternal UPD 6 (van den Berg-Loonen et aL, submitted for publication) are compatible with nor mal human development supports our previous finding that the IGF2R gene is not imprinted (Kalscheuer et aL, 1993) and raises the possibility that this holds for the MAS gene, too. Expression and methylation studies should soon clarify this point and may shed more light as in the absence or presence of a trans-acting factor on the role of gene-specific and regional factors in the acting as a repressor by binding to the hypomethylated control of parent-specific expression, paternal CpG 2 region may account for the differential expression of the human and mouse IG F2R genes.…”
Section: Cpg 1 Is Completely Unmethylated On Both Parental Igf2r Allesupporting
confidence: 77%
“…Differences in chromatin structure as well (Rabin et aL, 1987). The observation that paternal (Welch et aL, 1990) and maternal UPD 6 (van den Berg-Loonen et aL, submitted for publication) are compatible with nor mal human development supports our previous finding that the IGF2R gene is not imprinted (Kalscheuer et aL, 1993) and raises the possibility that this holds for the MAS gene, too. Expression and methylation studies should soon clarify this point and may shed more light as in the absence or presence of a trans-acting factor on the role of gene-specific and regional factors in the acting as a repressor by binding to the hypomethylated control of parent-specific expression, paternal CpG 2 region may account for the differential expression of the human and mouse IG F2R genes.…”
Section: Cpg 1 Is Completely Unmethylated On Both Parental Igf2r Allesupporting
confidence: 77%
“…IGF2R had previously been reported not to be imprinted in human fetal and postnatal tissues including kidney (Ogawa et al, 1993b;Kalscheuer et al, 1993), except in a small proportion of subjects as reported by our group (Xu et al, 1993) and others (Smrzka et al, 1995). Because it is impossible to obtain normal postnatal kidney, the signi®cance of IGF2R imprinting in Wilms' tumor can only be determined indirectly.…”
Section: Discussionmentioning
confidence: 53%
“…Alleles that make the gene susceptible to paternal-germline inactivation are in linkage disequilibrium with 164 and, probably, rarer alleles other than 162. The absence of repression in the paternal 164 in our non-imprinting patients, as well as normal 164 expression in the majority of unselected normal individuals (Xu et al, 1993;Ogawa et al, 1993b;Kalscheuer et al, 1993) would indicate that the frequency of the`imprintable' allele is much lower than that of 164. Alternatively, permissive cis alleles may be necessary but not su cient, imprinting additionally depending on a trans-locus or non-genetic factors.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…All reverse transcription reac tions were performed exactly as described previously (Kalscheuer et al, 1993).…”
Section: Methodsmentioning
confidence: 99%